MENINGKATKAN APRESIASI SENI MUSIK SISWA KELAS V PADA MATA PELAJARAN SENI BUDAYA DAN KETERAMPILAN MELALUI MEDIA ALAT MUSIK ANGKLUNG - Rohmatun, Yunia; Julia, Julia; Jayadinata, Asep Kurnia (Jurnal Pena Ilmiah, 2017)
This study is an effort in improving the art music appreciation of 5th grader students on the subjects of art, culture and media skills through the application of angklung. Research conducted on this occasion is a class action that was conducted in two cycles. The subjects were all students of 5th grader SDN Inklusif Sariwangi Cijambe Subang totaling 44 students. Source of data derived from students, teachers, peers, and researchers. Data collection technique used observation, documentation, and tests. The validity of the data using expert opinion. Analysis of the data used by the analysis of qualitative and quantitative analysis. Obtaining data from this study are very useful to improve the competence of teachers in developing the skills to play angklung as a medium of art music appreciation students in Kabupaten Subang. The results showed that through the application of media angklung music can enhance art appreciation 5th grader students on the subjects of art, culture and skills of the first cycle and the second cycle.